2006
DOI: 10.1002/jnr.20751
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study of the distribution of sodium‐dependent vitamin C transporters in adult rat brain

Abstract: Sodium-dependent vitamin C transporters (SVCTs) is known to transport the reduced form of ascorbic acid into the cell, whereas the oxidized form of vitamin C (VC) is moved through a facilitative sugar transporter, such as glucose transporter (GLUT). With regard to the distribution of SVCT1 and -2 within the various organs, they were reported to be expressed in different types of cells. Especially in the central nervous system, only SVCT2 mRNA was expressed mainly in neurons and some types of neuroglial cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
3
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 31 publications
(52 reference statements)
6
75
3
3
Order By: Relevance
“…Recently, several studies revealed the expression and transport activity of SVCT2 in a variety of nervous system compartments and cell types (Castro et al, 2001;Angelow et al, 2003;Garcia Mde et al, 2005;Mun et al, 2006;Qiu et al, 2007;Caprile et al, 2009;Harrison and May, 2009;Gess et al, 2011). We previously showed expression and activity of SVCT2 in Schwann cell cultures in vitro (Gess et al, 2010).…”
Section: Discussionmentioning
confidence: 88%
“…Recently, several studies revealed the expression and transport activity of SVCT2 in a variety of nervous system compartments and cell types (Castro et al, 2001;Angelow et al, 2003;Garcia Mde et al, 2005;Mun et al, 2006;Qiu et al, 2007;Caprile et al, 2009;Harrison and May, 2009;Gess et al, 2011). We previously showed expression and activity of SVCT2 in Schwann cell cultures in vitro (Gess et al, 2010).…”
Section: Discussionmentioning
confidence: 88%
“…Many studies indicate that SVCT2 is a transporter that is preferentially expressed in neurons from different areas in the adult brain, such as the cortex, hippocampus, hypothalamus, and cerebellar precursors [1,[7][8][9][10][11]. SVCT2 mediates uptake of AA, an important molecule for antioxidant defense and general metabolic needs of neurons.…”
Section: Distribution and Function Of Svct2 In The Adult Brainmentioning
confidence: 99%
“…Although SVCT2 was originally thought to be a neuronal transporter, there is increasing evidence demonstrating its expression in glial cells in the CNS [4,7,8,10,[12][13][14]. Indeed, SVCT2 has been reported in cortical microglia, where its function remains unknown [10]. In hypothalamic tanycytes, it may participate in maintaining the high parenchymal concentrations of vitamin C that characterize this region [8].…”
Section: Distribution and Function Of Svct2 In The Adult Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…SVCT2 proteininin erişkin sıçan beynindeki dağılımının incelendiği bir immünhistokimya çalışmasında ise protein yoğunluğunun serebral kortekste, hipokampusta ve serebellumda Purkinje hücrelerinde yoğun olduğu görülmüştür. [51] Diğer yandan hipokampal nö-ron kültüründe yapılan bir immünhistokimya çalışmasında SVCT2 boyanma-sının nöronların aksonlarında yoğunluk kazandığı gösterilerek, SVCT2' nin aksonal taşıyıcı ailesine ait olduğu iddia edilmiştir. SVCT2, nöronlardaki askorbik asit içeriğinin idamesini sağlayarak nöronal gelişimde ve nöronal işlevlerin matürasyonunda, eksitotoksisite ve oksidatif stresten korunmada önemli rol oynamaktadır.…”
Section: Sinyal Yolaklarının Psikiyatrik Hastalıkların Patogenezindekunclassified